Splenectomy: A strong risk factor for pulmonary hypertension in patients with thalassaemia - Phrommintikul A. (2014)
Objective: To determine the association between splenectomy and pulmonary hypertension in patients with thalassaemia with anaemia. Design: Prospective cross-sectional study. Methods: 68 patients with thalassaemia, who had a haemoglobin concentration of less than 100 g/l, were recruited into this study. Echocardiography was performed before clinical data were reviewed. Pulmonary artery pressure was estimated by measuring the systolic transtricuspid pressure gradient from tricuspid regurgitation and adding it to the right atrial pressure, which was estimated by the response of the inferior vena cava to inspiration. Pulmonary hypertension was defined as systolic pulmonary artery pressure > 35 mm Hg. History of splenectomy and other clinical data were compared between patients with and without pulmonary hypertension. Results: 29 patients had pulmonary hypertension and 39 did not. Patients with pulmonary hypertension had significantly more nucleated red blood cells and higher platelet counts, and a higher prevalence of splenectomy (75.8% v 25.6%, odds ratio 9.1, 95% confidence interval 3.0 to 27.7). In multivariate analysis, splenectomy was the only factor significantly related to pulmonary hypertension. Conclusion: Splenectomy is a strong risk factor for pulmonary hypertension in patients with thalassaemia.